Yttrium-aluminum-silicon glass, method for producing the same, and use thereof

CN122977704APending Publication Date: 2026-10-27HUAWEI TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510525311.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

当前,终端设备使用的防护玻璃仍以高铝玻璃或锂铝硅微晶玻璃为主,其弹性模量仅为70-90GPa、表面硬度仅为620-650Hv,跌落高度仅1-1.6m,而为获得高质量的玻璃盖板,要求玻璃盖板的弹性模量需达到120GPa以上,跌落高度在1.8m以上,由此可见,现有体系的玻璃已无法适应移动终端技术发展的要求

Benefits of technology

[0094]其中,本申请上述各可能实现方式中的数据,例如各组分的质量占比、晶粒尺寸、弹性模量、压应力、张应力等数据,在测量时,工程测量误差范围内的数值均应理解为在本申请所限定的范围内。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977704A_ABST
    Figure CN122977704A_ABST
Patent Text Reader

Abstract

The application provides a yttrium aluminum silicon glass, a preparation method and application thereof, so as to obtain a glass with high elastic modulus, high hardness and high anti-falling performance. The yttrium aluminum silicon glass comprises the following components in percentage by weight: Y2O3: 30%-45%, Al2O3: 15%-28%, SiO2: 25%-45%, ZrO2: 0.5%-8%, P2O5: 0.1%-2%, monovalent metal oxide: 0.5-10w%, the monovalent metal oxide comprising Li2O, TiO2: 0%-2%, Sb2O3: 0%-0.5%, CeO2: 0%-0.5%, divalent metal oxide: 0.1%-16%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of glass, specifically to a yttrium aluminum silicon glass, its preparation method, and its application. Background Technology

[0002] With the development of communication and electronic technologies, the trend towards larger, thinner, lighter, and foldable display screens for mobile terminals and wearable devices has become mainstream. Currently, the protective glass used in terminal devices is still mainly high-alumina glass or lithium aluminum silicon microcrystalline glass, with an elastic modulus of only 70-90 GPa, a surface hardness of only 620-650 Hv, and a drop height of only 1-1.6m. However, to obtain high-quality glass covers, the elastic modulus of the glass covers needs to reach above 120 GPa, and the drop height needs to be above 1.8m. It is evident that the existing glass system can no longer meet the requirements of mobile terminal technology development. Summary of the Invention

[0003] This application provides a yttrium aluminum silicon glass, its preparation method, and its application, to obtain a glass that combines high elastic modulus, high hardness, and high impact resistance.

[0004] In a first aspect, this application provides a yttrium aluminum silicon glass, wherein the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0005] Y2O3: 30%–45%,

[0006] Al2O3: 15%–28%,

[0007] SiO2: 25%–45%,

[0008] ZrO2: 0.5%–8%,

[0009] P2O5: 0.1%–2%,

[0010] Monovalent metal oxides: 0.5–10 wt%, including Li₂O.

[0011] TiO2: 0%–2%,

[0012] Sb₂O₃: 0%–0.5%,

[0013] CeO2: 0%–0.5%,

[0014] Divalent metal oxides: 0.1%–16%.

[0015] The yttrium aluminum silicon glass of this application uses SiO2 to form a network framework, and constructs a three-dimensional disordered network through a Si-O tetrahedral structure to provide structural stability. 3+ Can replace Si 4+It enters the network structure, forming Si-O and Al-O tetrahedra. 3+ It can compensate for the negative charge of Si-O and Al-O tetrahedra, reduce structural defects, improve structural compactness, and enhance thermal and chemical stability. Additionally, Y... 3+ The high electron density of ZrO2 can significantly increase the refractive index of glass, thereby improving its optical properties. ZrO2 mainly acts as a nucleating agent and promotes crystal precipitation, while P2O5 can improve the glass melting process and facilitate ion exchange in the open network structure during subsequent tempering. Adding optional TiO2 can help improve the phase transformation of glass, enhance the crystalline phase within the glass, and thus improve its mechanical properties. Adding optional Sb2O3 and CeO2 can reduce bubbles within the glass, thereby contributing to improved optical and mechanical properties. The addition of Li2O, Na2O, and K2O can help improve the chemical tempering strength of the glass, thereby improving its mechanical properties. The addition of divalent metal oxides can synergistically control the crystallization tendency within the glass, thus contributing to improved mechanical and optical properties. The yttrium aluminum silicon glass of this application, by adding the above-mentioned specific amounts of components, can achieve an elastic modulus of over 90 GPa. Yttrium aluminum silicon glass with the formulation of this application can undergo crystallization treatment to obtain microcrystalline glass. After crystallization, its elastic modulus can reach over 120 GPa, and further over 130 GPa. Furthermore, the yttrium aluminum silicon glass of this application can also be chemically strengthened through ion exchange. The microcrystalline glass after ion exchange can have an elastic modulus exceeding 1.5 × 10⁻⁶ GPa. 4 With a tensile stress linear density of MPa / mm, the drop performance of glass-ceramics can be improved to 1.8m. This demonstrates enormous application potential in display devices and wearable devices.

[0016] In one implementation, the mass percentage of Y₂O₃ in the yttrium aluminum silicon glass is 32% to 45%. Increasing the Y₂O₃ content can further improve the elastic modulus and drop resistance of the yttrium aluminum silicon glass.

[0017] In one implementation, the mass percentage of Al2O3 in the yttrium aluminum silicon glass is 15% to 25%. By controlling the aluminum content of alumina, it can be combined with a high content of yttrium oxide to improve the glass-forming properties of the yttrium aluminum silicon glass.

[0018] In one implementation, the mass percentage of SiO2 in the yttrium aluminum silicon glass is 25% to 40%. By controlling the SiO2 content, it works in conjunction with yttrium oxide and aluminum oxide to improve the stability of the glass framework structure and enhance the mechanical properties of the glass.

[0019] In one implementation, the divalent metal oxide includes at least one of MgO, CaO, ZnO, and BaO.

[0020] MgO, CaO, ZnO, and BaO can help improve the synergistic effect between them, which can effectively regulate the properties of glass materials, control the tendency of glass to crystallize, and avoid crystallization during the forming process, thus avoiding difficulties in production.

[0021] In one implementation, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0022] Y2O3: 30%–45%,

[0023] Al2O3: 15%–25%,

[0024] SiO2: 25%–40%,

[0025] ZrO2: 0.5%–8%,

[0026] P2O5: 0.1%–2%,

[0027] Monovalent metal oxides: 1.0–10%, wherein the monovalent metal oxides include Li₂O and Na₂O, wherein the mass percentage of Li₂O is 0.5–6%, and the mass percentage of Na₂O is 0.5–6%.

[0028] TiO2: 0%–2%,

[0029] Sb₂O₃: 0%–0.5%,

[0030] CeO2: 0.1%–0.5%,

[0031] Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

[0032] In one implementation, the monovalent metal oxide contains Li₂O and Na₂O, with Li₂O accounting for 3-12% by mass and Na₂O accounting for 1.5-9% by mass.

[0033] In one implementation, the elastic modulus of the yttrium aluminum silicon glass is greater than 90 GPa.

[0034] This elastic modulus is the elastic modulus of yttrium oxide glass before crystallization and chemical strengthening treatment, and it is also the elastic modulus of the base glass. Its bending strength can reach 600 MPa and above, which can help to obtain yttrium aluminum silicon glass with higher elastic modulus.

[0035] In one implementation, the yttrium aluminum silicon glass is a microcrystalline glass, and the yttrium aluminum silicon glass contains a crystalline phase, the crystalline phase including Zr. x Y y O 2x+1.5y, ZrO2, ZnAl2O4, MgAl2O4, Y2Si2O7, Y4Zr3O 12 Ba 0.808 Al 1.71 Si 2.99 At least one of O8, spodumene, and quartz solid solution; x ranges from 0.72 to 0.95, and y ranges from 0.06 to 0.28. The crystalline phase accounts for 30% to 80% of the volume of the yttrium aluminum silicon glass.

[0036] The yttrium aluminum silicon glass of this application can be crystallized into a microcrystalline glass. This microcrystalline glass contains at least one or more crystalline phases, which improve the mechanical and optical properties of the yttrium aluminum silicon glass. The total volume of the crystalline phases in the yttrium aluminum silicon glass can be 30%-80% of its total volume. By controlling the volume percentage of the crystalline phases, a range of glass transparency can be obtained, thereby expanding the application scenarios of yttrium aluminum silicon glass, such as its use in front panels or back covers of terminal devices. When used in front panels, the crystal percentage can be controlled within a low range to obtain glass with high light transmittance. When used in back covers, the crystal percentage can be controlled within a high range to obtain glass with high mechanical properties.

[0037] In one implementation, the crystalline phase is nanocrystal, and the grain size of the crystalline phase is 10-200 nm. If the size of the nanocrystal is too large, it will affect the light transmittance of the glass; if the size of the nanocrystal is too small, it will have little effect on improving the mechanical properties of the glass. When the size of the nanocrystal is controlled within the range of 10-200 nm, it can effectively improve the mechanical properties of the glass and improve the light transmittance.

[0038] In one implementation, the yttrium aluminum silicon glass is chemically tempered glass, and the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0039] Y2O3: 30%–45%,

[0040] Al2O3: 25%–28%,

[0041] SiO2: 25%–45%,

[0042] ZrO2: 0.5%–8%,

[0043] P2O5: 0.1%–2%,

[0044] Monovalent metal oxides: 1.5–10%, wherein the monovalent metal oxides include Li₂O, Na₂O, and K₂O, wherein the mass percentage of Li₂O is 0.5–6%, the mass percentage of Na₂O is 0.5–6%, and the mass percentage of K₂O is 0.5–6%.

[0045] TiO2: 0%–2%,

[0046] Sb₂O₃: 0%–0.5%,

[0047] CeO2: 0.1%–0.5%,

[0048] Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

[0049] In one implementation, the stress layer depth of the yttrium aluminum silicon glass is greater than or equal to 120 μm. After tempering, the stress layer of the yttrium aluminum silicon glass of this application can reach over 120 micrometers, thereby effectively improving the glass's impact resistance.

[0050] In one implementation, the yttrium aluminum silicon glass has an elastic modulus greater than or equal to 140 GPa, a compressive stress CS50 at 50 μm greater than 200 MPa, an average tensile stress CT.av in the tensile stress zone greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm, falling ball impact energy greater than 0.2J, transmittance greater than 88%, drop failure height under 80 grit sandpaper greater than 1.8m.

[0051] Secondly, this application provides a yttrium aluminum silicon glass, wherein the yttrium aluminum silicon glass is a microcrystalline glass, and the microcrystalline glass contains a crystalline phase, the crystalline phase including γ-rays. y Zr x O 1.5y+2x Zr x Y y O 2x+1.5y , ZrO2, ZnAl2O4, MgAl2O4, Y2Si2O7, Y4Zr3O 12 Ba 0.808 Al 1.71 Si 2.99 At least one of O8, spodumene, and quartz solid solution; the crystalline phase accounts for 30-80% of the volume of the yttrium aluminum silicon glass; the crystalline phase is nanocrystalline and the grain size of the crystalline phase is 10-200 nm.

[0052] The yttrium aluminum silicon glass of this application is a microcrystalline glass, in which microcrystals are formed internally, and the crystal phase structure may include Ya. y Zr x O 1.5y+2x Zr x Y y O 2x+1.5y , ZrO2, ZnAl2O4, MgAl2O4, Y2Si2O7, Y4Zr3O 12 Ba 0.808 Al1.71 Si 2.99 By forming the above crystalline phases inside the glass and controlling the grain size of the crystalline phases within the range of 10-200 nm, the hardness and mechanical properties of the glass can be improved, thereby improving the drop resistance of the glass.

[0053] In one implementation, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0054] Y2O3: 30%–45%,

[0055] Al2O3: 15%–28%,

[0056] SiO2: 25%–45%,

[0057] ZrO2: 0.5%–8%,

[0058] P2O5: 0.1%–2%,

[0059] Monovalent metal oxides: 0.5–10 wt%, including Li₂O.

[0060] TiO2: 0%–2%,

[0061] Sb₂O₃: 0%–0.5%,

[0062] CeO2: 0%–0.5%,

[0063] Divalent metal oxides: 0.1%–16%.

[0064] SiO2 forms the network framework, and a three-dimensional disordered network is constructed through the Si-O tetrahedral structure, providing structural stability. Al 3+ Can replace Si 4+ It enters the network structure, forming Si-O and Al-O tetrahedra. 3+ It can compensate for the negative charge of Si-O and Al-O tetrahedra, reduce structural defects, improve structural compactness, and enhance thermal and chemical stability. Additionally, Y... 3+The high electron density of ZrO2 can significantly increase the refractive index of glass, thereby improving its optical properties. ZrO2 mainly acts as a nucleating agent and promotes crystal precipitation, while P2O5 can improve the glass melting process and facilitate ion exchange in the open network structure during subsequent tempering. Adding optional TiO2 can help improve the phase transformation of glass, enhance the crystalline phase within the glass, and thus improve its mechanical properties. Adding optional Sb2O3 and CeO2 can reduce bubbles within the glass, thereby contributing to improved optical and mechanical properties. The addition of Li2O, Na2O, and K2O can help improve the chemical tempering strength of the glass, thereby improving its mechanical properties. The addition of divalent metal oxides can synergistically control the crystallization tendency within the glass, thus contributing to improved mechanical and optical properties. The yttrium aluminum silicon glass of this application, by adding the above-mentioned specific amounts of components, can achieve an elastic modulus of over 90 GPa. Yttrium aluminum silicon glass with the formulation of this application can undergo crystallization treatment to obtain microcrystalline glass. Furthermore, the yttrium aluminum silicon glass of this application can also be chemically strengthened through ion exchange. After crystallization and chemical strengthening, its elastic modulus can reach over 120 GPa. The microcrystalline glass after ion exchange can have a modulus exceeding 1.5 × 10⁻⁶. 4 With a tensile stress linear density of MPa / mm, the drop performance of glass-ceramics can be improved to 1.8m. This demonstrates enormous application potential in display devices and wearable devices.

[0065] In one implementation, the yttrium aluminum silicon glass is chemically tempered glass, and the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0066] Y2O3: 30%–45%,

[0067] Al2O3: 15%–28%,

[0068] SiO2: 25%–45%,

[0069] ZrO2: 0.5%–8%,

[0070] P2O5: 0.1%–2%,

[0071] Monovalent metal oxides: 1.5–10%, wherein the monovalent metal oxides include Li₂O, Na₂O, and K₂O, wherein the mass percentage of Li₂O is 0.5–6%, the mass percentage of Na₂O is 0.5–6%, and the mass percentage of K₂O is 0.5–6%.

[0072] TiO2: 0%–2%,

[0073] Sb₂O₃: 0%–0.5%,

[0074] CeO2: 0.1%–0.5%,

[0075] Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

[0076] By strengthening the glass, K ions are used to replace Li and Na in the glass to form a compressive stress layer on the glass surface, thereby further improving the strength of the glass.

[0077] In one implementation, the mass percentage of Y₂O₃ in the yttrium aluminum silicon glass is 32% to 45%. Increasing the Y₂O₃ content can further improve the elastic modulus and drop resistance of the yttrium aluminum silicon glass.

[0078] In one implementation, the mass percentage of Al2O3 in the yttrium aluminum silicon glass is 15% to 25%. By controlling the aluminum content of alumina, it can be combined with a high content of yttrium oxide to improve the glass-forming properties of the yttrium aluminum silicon glass.

[0079] In one implementation, the mass percentage of SiO2 in the yttrium aluminum silicon glass is 25% to 40%. By controlling the SiO2 content, it works in conjunction with yttrium oxide and aluminum oxide to improve the stability of the glass framework structure and enhance the mechanical properties of the glass.

[0080] In one implementation, the divalent metal oxide includes at least one of MgO, CaO, ZnO, and BaO.

[0081] In one implementation, the yttrium aluminum silicon glass has an elastic modulus greater than or equal to 140 GPa, a compressive stress CS50 at 50 μm greater than 200 MPa, an average tensile stress CT.av in the tensile stress zone greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm, impact height of falling ball greater than 0.2J, transmittance greater than 88%, drop failure height under 80 grit sandpaper greater than 1.8m.

[0082] Thirdly, this application provides a method for preparing yttrium aluminum silicon glass, the method comprising:

[0083] A glass substrate is prepared, comprising the following components in the indicated mass percentages: Y₂O₃: 30%–45%, Al₂O₃: 15%–28%, SiO₂: 25%–45%, ZrO₂: 0.5%–8%, P₂O₅: 0.1%–2%, monovalent metal oxides: 0.5%–10 wt%, wherein the monovalent metal oxides include Li₂O, TiO₂: 0%–2%, Sb₂O₃: 0%–0.5%, CeO₂: 0%–0.5%, and divalent metal oxides: 0.1%–16%.

[0084] The glass substrate is subjected to a first heat treatment and a second heat treatment to obtain microcrystalline glass. The temperature of the first heat treatment is 600-800℃ and the heat treatment time is 0.5-60h; the temperature of the second heat treatment is 750-900℃ and the heat treatment time is 0.5-4h.

[0085] The yttrium aluminum silicate glass obtained using the preparation method of this application is a glass-ceramic. Through the synergistic effect of the components, it is possible to prepare high-quality glass with a high yttrium oxide content, and by optimizing the heat treatment process, glass-ceramic with controllable grain size can be obtained. In the first heat treatment stage, the glass substrate undergoes nucleation, allowing for sufficient nucleation and the precipitation of a large number of crystal nuclei. In the second heat treatment stage, the glass is further heated to 750-900℃ and held for 0.5-4 hours to crystallize. This process benefits from the thorough heat treatment in the nucleation stage, resulting in the precipitation of a large number of uniform crystal nuclei in the glass-ceramic, enabling the rapid precipitation of a large number of uniformly distributed nanocrystals in the crystallization stage, thereby shortening the crystallization time and saving energy. By controlling the heat treatment process, the grain size in the glass-ceramic can be controlled within the range of 10-200 nm, thereby improving the mechanical and optical properties of the glass. Therefore, the heat treatment in the preparation method of this application enables the glass to undergo sufficient nucleation and rapid crystallization, and obtain uniformly distributed nanocrystalline crystals, so that the transmittance of the glass-ceramic exceeds 88% and the elastic modulus of the glass-ceramic exceeds 140 GPa.

[0086] In one implementation, the preparation method further includes the step of subjecting the microcrystalline glass after the second heat treatment to a first ion exchange treatment and a second ion exchange treatment in sequence;

[0087] The first ion exchange treatment includes: placing the microcrystalline glass in a first molten salt and exchanging it at 450-550°C for 1-20 hours; the first molten salt comprises the following components by weight percentage: 50-70 wt% sodium nitrate, 20-40 wt% potassium nitrate, 0-5 wt% lithium nitrate, 0.5-2 wt% alumina, 0.5-2 wt% diatomaceous earth, and 0.5-2 wt% antimony trioxide;

[0088] The second ion exchange treatment includes: placing the microcrystalline glass in a second molten salt and exchanging it at 480–600°C for 0.5–20 h; the second molten salt comprises the following components by weight percentage: 50–70 wt% potassium nitrate, 20–40 wt% sodium nitrate, 0–5 wt% cesium nitrate, 0.5–2 wt% alumina, 0.5–2 wt% diatomaceous earth, 0.5–2 wt% antimony trioxide, and 0.5–2 wt% potassium hydroxide.

[0089] In the preparation method of this application, chemical strengthening through ion exchange can further improve the mechanical properties of the glass. The ion-exchanged microcrystalline glass exhibits a stress layer depth exceeding 120 μm, a Cs50 greater than 200 MPa, a CT.av greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm, ball impact height greater than 0.2J, and overall drop height exceeding 1.8m.

[0090] Fourthly, this application provides a display screen comprising the yttrium aluminum silicon glass of this application, or yttrium aluminum silicon glass obtained using the preparation method of this application.

[0091] Fifthly, this application provides a structural component comprising the yttrium aluminum silicon glass of this application, or yttrium aluminum silicon glass obtained using the preparation method of this application. In addition to the yttrium aluminum silicon glass of this application, the structural component may also include components such as an encapsulation frame and an encapsulation housing for fixing the yttrium aluminum silicon glass.

[0092] Sixthly, this application provides an electronic device, which includes the display screen or structural components of this application.

[0093] The technical effects that can be achieved in aspects four through six above can be referred to the corresponding effect descriptions in aspect one above, and will not be repeated here.

[0094] In this application, the data in the various possible implementations mentioned above, such as the mass percentage of each component, grain size, elastic modulus, compressive stress, tensile stress, etc., should be understood as being within the range defined in this application, even if the values ​​are within the engineering measurement error range. Attached Figure Description

[0095] Figure 1 This is a schematic diagram of the structure of a mobile phone according to one embodiment;

[0096] Figure 2 This is the DSC curve diagram for Example 3;

[0097] Figure 3 The XRD patterns of the microcrystalline glass in Examples 2-5 are shown below.

[0098] Figure 4 The XRD patterns of the microcrystalline glass in Comparative Examples 2-5 are shown.

[0099] Figure 5 This is a SEM image of the microcrystalline glass in Example 5.

[0100] Figure label:

[0101] 100 - Terminal equipment; 10 - Middle frame; 20 - Glass cover. Detailed Implementation

[0102] To make the objectives, technical solutions, and advantages of this application clearer, the application will now be described in further detail with reference to the accompanying drawings.

[0103] The terminology used in the following embodiments is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. As used in the specification and appended claims of this application, the singular expressions “a,” “an,” “the,” “the,” and “this” are intended to also include expressions such as “one or more,” unless the context clearly indicates otherwise.

[0104] References to "one embodiment" or "some embodiments" as described in this specification mean that one or more embodiments of this application include a specific feature, structure, or characteristic described in connection with that embodiment. Therefore, the phrases "in one embodiment," "in some embodiments," "in other embodiments," "in still other embodiments," etc., appearing in different parts of this specification do not necessarily refer to the same embodiment, but rather mean "one or more, but not all, embodiments," unless otherwise specifically emphasized. The terms "comprising," "including," "having," and variations thereof mean "including but not limited to," unless otherwise specifically emphasized.

[0105] Yttrium aluminum silicate glass, or Yttrium aluminum silicon glass for short, is a novel glass system. The addition of yttrium oxide (Y₂O₃) improves the glass's mechanical properties and hardness, and allows for control over its light transmittance. However, due to the high melting point of yttrium oxide, when its content exceeds a certain level, such as exceeding 30% by mass, it can severely affect the glass's forming and processing properties and deteriorate its optical properties.

[0106] The yttrium aluminum silicon glass of this application, through the rational setting of the proportions of various elements, can achieve both good processing performance and adjustable light transmittance and mechanical properties, making it suitable, but not limited to, as a protective material to meet various application scenarios. For example, it can be applied to various mobile terminals or electronic products, such as serving as glass covers for mobile terminals, smart wearable devices, or other electronic products. Mobile terminal products include, but are not limited to, mobile office, smart home, sports and health, audio-visual entertainment, and smart travel-related electronic terminal devices such as mobile phones, tablets, desktop computers, laptops, smart screens, monitors, speakers, glasses, watches, headphones, and automotive products. It is understood that, in addition to terminal devices, this glass product can also be used for other products requiring surface protection.

[0107] Understandably, in addition to terminal equipment, this glass product can also be used for other products that require surface protection.

[0108] It is also understandable that, depending on the application scenario, the glass of this application can also be crystallized to obtain microcrystalline glass, or it can be directly chemically strengthened to obtain reinforced glass.

[0109] The following explanation uses a mobile phone as an example. Figure 1 This is a schematic diagram of the structure of a mobile phone according to one embodiment. Please refer to [link / reference]. Figure 1 The terminal device 100 can be a mobile phone, and the terminal device 100 includes a mid-frame 10 and a glass cover 20 connected to the mid-frame 10. The glass cover can be the front cover of the mobile phone or the back cover of the mobile phone.

[0110] The glass cover may include a glass substrate and an optional functional film layer disposed on at least one side of the glass substrate.

[0111] Since the glass cover plate needs to serve as the encapsulation cover for the terminal device, the glass substrate must not only possess good optical properties but also good mechanical properties, such as high elastic modulus and strength, to ensure the terminal device meets drop resistance requirements. Based on this, the glass substrate in the glass cover plate of this application embodiment is a yttrium aluminum silicate glass, hereinafter referred to as yttrium aluminum silicate glass. In this application embodiment, by controlling the component ratio, the yttrium aluminum silicate glass can produce a glass sheet with an elastic modulus greater than 90 GPa after molding. After microcrystalline treatment and strengthening treatment, the mechanical properties and drop resistance can be further improved, such as an elastic modulus exceeding 140 GPa and a tensile stress linear density exceeding 1.5 × 10⁻⁶. 4 MPa / mm, drop performance can be improved to 1.8m.

[0112] The yttrium aluminum silicon glass provided in this application embodiment comprises the following components by weight percentage based on the total weight of the yttrium aluminum silicon glass:

[0113] Y2O3: 30%–45%,

[0114] Al2O3: 15%–28%,

[0115] SiO2: 25%–45%,

[0116] ZrO2: 0.5%–8%,

[0117] P2O5: 0.1%–2%,

[0118] Monovalent metal oxides: 0.5–10 wt%, including Li₂O.

[0119] TiO2: 0%–2%,

[0120] Sb₂O₃: 0%–0.5%,

[0121] CeO2: 0%–0.5%,

[0122] Divalent metal oxides: 0.1%–16%.

[0123] In one embodiment, the monovalent metal oxide contains Li2O and Na2O, with Li2O accounting for 3-12% by mass and Na2O accounting for 1.5-9% by mass.

[0124] The yttrium aluminum silicon glass in this application mainly contains at least one of yttrium oxide (Y2O3), aluminum oxide (Al2O3), silicon oxide (SiO2), zirconium oxide (ZrO2), phosphorus pentoxide (P2O5), lithium oxide (Li2O), sodium oxide (Na2O), and potassium oxide (K2O). The forming properties, mechanical properties, and optical properties of the yttrium aluminum silicon glass can be controlled by adding optional components such as titanium oxide (TiO2), antimony oxide (Sb2O3), cerium oxide (CeO2), and divalent metal oxides.

[0125] The yttrium aluminum silicon glass provided in this application embodiment may include some unavoidable impurities in addition to the components mentioned above. The sum of the mass percentages of each component in the yttrium aluminum silicon glass of this application embodiment and the sum of the mass percentages of the unavoidable impurities are 100%.

[0126] The functions of each component in the yttrium aluminum silicon glass of this application will be explained below.

[0127] Alumina Al2O3

[0128] In the presence of sufficient free oxygen, Al₂O₃ can participate in the construction of the glass network structure, which is beneficial to improving the strength and chemical stability of the glass. Furthermore, an appropriate amount of Al₂O₃ is conducive to ion exchange in glass-ceramics. However, if the Al₂O₃ content is too low, the glass network structure is loose, resulting in lower strength and chemical stability. Conversely, if the Al₂O₃ content is too high, the glass network structure becomes too dense, making crystal precipitation and growth difficult, thus affecting the formation of glass-ceramics. When the Al₂O₃ mass content is between 15% and 28%, the strength and chemical stability of glass-ceramics can be effectively improved.

[0129] In this embodiment of the application, the mass percentage of Al2O3 can be 15% to 25%, or 18% to 25%. For example, the mass percentage of Al2O3 can be any two values ​​between 15%, 16%, 17%, 18%, 19%, 20%, 22%, 25%, 27%, 28%, etc.

[0130] silicon dioxide (SiO2)

[0131] In aluminosilicate glass, silicon dioxide (SiO2) is mainly used to form the glass's network structure, improving its chemical and thermal stability. If the SiO2 content is too low, the glass-forming performance deteriorates, its chemical stability worsens, it is prone to phase separation, and it may even be impossible to form glass. Therefore, in the embodiments of this application, the lower limit of the SiO2 content can be 25% or more, and more specifically 28% or more. However, when the SiO2 content is too high, the melting and crystallization control of the glass-ceramic becomes difficult. Therefore, the upper limit of the SiO2 content can be limited to below 45%, and more specifically below 42%.

[0132] In the glass substrate of this application embodiment, the mass percentage of SiO2 can be 25-45%, for example, 28-42%, or for example, 28%-40%. Exemplarily, the mass percentage of SiO2 can be any two values ​​between 25%, 26%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, or more. In this application embodiment, by controlling the mass percentage of SiO2, the basic mechanical properties and high light transmittance of yttrium aluminum silicon glass can be achieved, enabling yttrium aluminum silicon glass to achieve high transmittance in the visible light range.

[0133] Yttrium oxide (Y2O3)

[0134] Y₂O₃, as an essential component of the yttrium aluminum silicon glass in this application embodiment, can effectively fill the glass gaps and improve the packing degree of the glass network structure. Furthermore, as a raw material, Y₂O₃ can form a Zr-based structure after heat treatment. x Y y O 2x+1.5y A crystalline phase with at least one of ZrO2 as a main component can improve the hardness, elastic modulus, and fracture toughness of glass-ceramics, thereby enhancing their scratch resistance and impact resistance. However, excessively high yttrium oxide content can increase the refractive index and decrease the transmittance of glass-ceramics, making them unsuitable for use in mobile terminals. Therefore, the yttrium oxide content needs to be controlled within a certain range to balance the optical and mechanical properties of the glass-ceramics. Through extensive experimental research, the composition range of Y2O3 was determined: a lower limit of 30% and an upper limit of 45%. If it is too high, such as above 45%, the high melting point of Y2O3 makes the melting of glass components more difficult, and the resulting glass-ceramics after crystallization will have a higher refractive index and lower transmittance.

[0135] In this embodiment of the application, the mass percentage of Y2O3 can be 30% to 45%, or for example, 31% to 45%, or for example, 32% to 42%. Exemplarily, the mass percentage of Y2O3 can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or any value between any two of the above.

[0136] Zirconium oxide (ZrO2)

[0137] ZrO2, as an essential component of the yttrium aluminum silicon glass in this application, primarily serves two purposes: first, as a nucleating agent, it enables uniform crystallization of the glass, effectively controlling crystal precipitation and size to prevent excessively large crystals from affecting optical performance; second, it improves the chemical stability of the base glass or glass-ceramic even with relatively high Li content. Furthermore, experimental research has shown that ZrO2 can effectively reduce the risk of devitrification during the forming process of the base glass.

[0138] In this embodiment of the application, the mass percentage of ZrO2 can be 0.5% to 8%, or 1% to 7%, or 2% to 7%, or 3% to 6%. For example, the mass percentage of ZrO2 can be any two values ​​between 0.5%, 0.7%, 1%, 1.2%, 1.5%, 1.8%, 2%, 2.3%, 2.5%, 2.7%, 3%, 3.5%, 3.8%, 4%, 4.2%, 4.5%, 4.8%, 5%, 5.2%, 5.5%, 5.8%, 6%, 6.2%, 6.5%, 6.8%, 7%, 7.2%, 7.5%, 7.8%, or 8% or more.

[0139] Phosphorus pentoxide (P2O5)

[0140] P2O5 is an essential component of the yttrium aluminum silicon glass in the embodiments of this application. Its introduction can increase the amount of zirconium oxide introduced and make the glass network looser due to the effect of π bonds. Therefore, a small amount of P2O5 can lower the melting temperature of the glass and improve the ion exchange efficiency. However, excessive P2O5 content can lead to phase separation in the glass, affecting optical properties and even causing devitrification.

[0141] In this embodiment of the application, the mass percentage of P2O5 can be 0.1% to 2%, or for example, 0.2% to 1.5%, or for example, 0.3% to 1.2%. Exemplarily, the mass percentage of P2O5 can be any two values ​​between 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, and 1.5%.

[0142] Lithium oxide (Li2O)

[0143] Li2O, as an essential component of the yttrium aluminum silicon glass in the embodiments of this application, can reduce the viscosity of the glass to facilitate melting. It is also a major component in the ion exchange process, replacing sodium and potassium ions. It can increase the depth of chemical ion strengthening compressive stress. However, if its content is too low, it will not only be detrimental to the glass melting effect, but also make it difficult to obtain a deep ion exchange depth.

[0144] In this embodiment, the Li2O content is controlled within the range of 0.5% to 10%, or for example, within the range of 1% to 8%, or for example, within the range of 2% to 7%. This allows the yttrium aluminum silicon glass to have high transmittance and structural strength, ensuring that the transmittance and structural strength of the yttrium aluminum silicon glass meet the requirements for use as a glass cover. Exemplarily, the mass percentage of Li2O in the yttrium aluminum silicon glass can be any two values ​​between 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 5%, 7%, 8%, 10%, or more.

[0145] Sodium oxide (Na2O)

[0146] Na2O is an optional component of the yttrium aluminum silicon glass in this application embodiment, which is significantly different from the low Na2O content of general microcrystalline glass. As the outer body of the glass network, Na2O mainly plays the role of breaking the network and providing free oxygen, and has a strong effect of inhibiting crystal precipitation. Generally, the Na2O content of microcrystalline glass is low, which is beneficial to crystallization. However, if the Na2O content is too low in this application embodiment, the exchange content of Na ions and K ions in the microcrystalline glass is insufficient during ion exchange, resulting in a low surface compressive stress value and affecting the strength. Therefore, in this application embodiment, the Na2O content can be more than 1%, and more than 1.5%.

[0147] In this embodiment, when the yttrium aluminum silicon glass contains Na₂O, the mass percentage of Na₂O can be in the range of 0.5-10%, for example, in the range of 0.5-8%, or for example, in the range of 1%-5%. This allows the yttrium aluminum silicon glass to have high transmittance and structural strength, ensuring that the transmittance and structural strength of the yttrium aluminum silicon glass meet the requirements for use as a glass cover. For example, the mass percentage of Li₂O in the glass substrate can be any two values ​​between 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 2%, 3%, 5%, 7%, 8%, 10%, or more.

[0148] It should be noted that when yttrium aluminum silicon glass contains both Li2O and Na2O, the total content of Li2O and Na2O must be controlled within the range of 0.5% to 10%.

[0149] Potassium oxide (K2O)

[0150] K2O is an optional component of the yttrium aluminum silicon glass in this application embodiment. The addition of K2O can lower the melting temperature of the glass raw material, improve the melting quality, and improve the optical properties of the glass-ceramic. In addition, when K2O and Na2O are added together, the addition of K2O is also beneficial to increase the ion exchange depth during the chemical strengthening process, thereby improving the mechanical and optical properties of the chemically strengthened glass-ceramic.

[0151] Adding Li₂O to the glass composition can significantly lower the glass melting temperature, improve melt quality, and enhance glass forming. When both P₂O₅ and K₂O are introduced, it promotes deeper ion exchange during chemical strengthening. However, excessively high Li₂O content can negatively impact the chemical stability of the glass and adversely affect the glass-ceramic forming process.

[0152] When yttrium aluminum silicon glass contains Li2O, Na2O and K2O simultaneously, the total content of Li2O, Na2O and K2O must be controlled within the range of 0.5% to 10%.

[0153] Titanium oxide (TiO2)

[0154] TiO2 is an optional component of the yttrium aluminum silicon glass in the embodiments of this application. It is introduced as a nucleating agent to improve the nucleation rate of the glass-ceramic. However, if the amount introduced is too large, it will cause the glass-ceramic to become colored.

[0155] TiO2, ZrO2, and P2O5 are not only nucleating agents but also beneficial for ion exchange. Under their combined action, P2O5 and TiO2 help increase the depth of ion exchange, while ZrO2 helps increase the compressive stress value.

[0156] In this embodiment of the application, the mass percentage of TiO2 can be 0-2%, for example, 0.01-2%, 0.05-1%, or 0.1%-0.8%. Exemplarily, the mass percentage of TiO2 can be any two values ​​between 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, or 1.5%.

[0157] Antimony oxide Sb2O3

[0158] Sb2O3 can be used as a clarifying agent. The addition of Sb2O3 helps to reduce the formation of gas defects in the glass melt, reduce the number of melt bubbles, and improve the clarifying effect.

[0159] In this embodiment of the application, the mass percentage of Sb2O3 can be 0-0.5%, or for example, 0.1-0.5%, 0.2-0.5%, or 0.2-0.3%. For example, the mass percentage of Sb2O3 can be any two values ​​between 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%.

[0160] Cerium oxide (CeO2)

[0161] CeO2 can be used as a clarifying agent. The addition of CeO2 helps to reduce the formation of gas defects in the glass melt, reduce the number of melt bubbles, and improve the clarifying effect. At the same time, it can further reduce the glass melting temperature, improve the melting quality, and improve the glass forming performance, so as to obtain a uniform and defect-free parent glass and form a suitable crystal phase during the crystallization process.

[0162] In this embodiment of the application, the mass percentage of CeO2 can be 0 to 0.5%, or for example, 0.1 to 0.5%, or for example, 0.2 to 0.5%, or for example, 0.2 to 0.3%. Exemplarily, the mass percentage of CeO2 can be any two values ​​between 0.01%, 0.05%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, or 0.5%.

[0163] Divalent metal oxides

[0164] Divalent metal oxides may include at least one of MgO, CaO, ZnO, and BaO.

[0165] ZnO can be used as an optional component. Its introduction can improve the melting, nucleation and crystallization properties of glass. However, when the amount introduced is too large, the glass is prone to phase separation.

[0166] In this embodiment of the application, when ZnO is added to the glass, the mass percentage of ZnO can be 0.1% to 2%, for example, 0.5% to 2%, for example, 0.5% to 1.5%, for example, 0.5% to 1.2%. Exemplarily, the mass percentage of ZnO can be any two values ​​between 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, 1.5%, 1.7%, 2%.

[0167] MgO, CaO, and BaO are optional components in this base glass. Their introduction is beneficial to improving the melting and forming of the glass. However, when the amount introduced is too large, the glass is prone to phase separation and is not conducive to ion exchange.

[0168] In this embodiment of the application, when MgO is added to the glass, the mass percentage of MgO can be 0.01-6%, for example, 0.5-5%, for example, 0.5-4%, for example, 0.5%-3.5%. Exemplarily, the mass percentage of MgO can be any two values ​​between 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, 1.5%, 1.7%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or more.

[0169] In this embodiment of the application, when CaO is added to the glass, the mass percentage of CaO can be 0.01% to 6%, for example, 0.5% to 5%, for example, 0.5% to 4%, for example, 0.5% to 3.5%. Exemplarily, the mass percentage of CaO can be any two values ​​between 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, 1.5%, 1.7%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or more.

[0170] In this embodiment of the application, when BaO is added to the glass, the mass percentage of BaO can be 0.01-6%, for example, 0.5-5%, for example, 0.5-4%, for example, 0.5%-3.5%. Exemplarily, the mass percentage of BaO can be any two values ​​between 0.01%, 0.02%, 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4%, 0.45%, 0.5%, 0.5%, 0.7%, 0.8%, 1.0%, 1.2%, 1.5%, 1.7%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, or more.

[0171] In one embodiment, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0172] Y2O3: 30%–45%,

[0173] Al2O3: 15%–25%,

[0174] SiO2: 25%–40%,

[0175] ZrO2: 0.5%–8%,

[0176] P2O5: 0.1%–2%,

[0177] Monovalent metal oxides: 0.5-10%, wherein the monovalent metal oxides include Li₂O, and the mass percentage of Li₂O is 0.5-6%.

[0178] TiO2: 0%–2%,

[0179] Sb₂O₃: 0%–0.5%,

[0180] CeO2: 0.1%–0.5%,

[0181] Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

[0182] In another embodiment, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0183] Y2O3: 30%–45%,

[0184] Al2O3: 15%–28%,

[0185] SiO2: 25%–45%,

[0186] ZrO2: 0.5%–8%,

[0187] P2O5: 0.1%–2%,

[0188] Li2O 0.5%–6%,

[0189] Na2O 0%~6%,

[0190] K2O 0%~2%,

[0191] The total content of Li₂O, Na₂O, and K₂O is 0.5–10 wt%.

[0192] MgO: 0%–6%,

[0193] ZnO: 0.5%–6%,

[0194] CaO: 0%–6%,

[0195] BaO: 0%–6%,

[0196] The total content of divalent metal oxides such as MgO, ZnO, CaO, and BaO is 0.5%–20%.

[0197] TiO2: 0%–2%,

[0198] Sb₂O₃: 0%–0.5%,

[0199] CeO2: 0.1%–0.5%.

[0200] In another embodiment, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0201] Y2O3: 30%–45%,

[0202] Al2O3: 15%–25%,

[0203] SiO2: 25%–40%,

[0204] ZrO2: 0.5%–8%,

[0205] P2O5: 0.1%–2%,

[0206] Li2O 0.5%–6%,

[0207] Na2O 0.1%~6%,

[0208] K2O 0%~2%,

[0209] The total content of Li₂O, Na₂O, and K₂O is 0.6–10 wt%.

[0210] MgO: 0.1%–6%,

[0211] ZnO: 0.5%–6%,

[0212] CaO: 0.1%–6%,

[0213] BaO: 0.1%–6%,

[0214] The total content of divalent metal oxides such as MgO, ZnO, CaO, and BaO is 0.%–20%.

[0215] TiO2: 0.05%–0.5%,

[0216] Sb₂O₃: 0.1%–0.5%,

[0217] CeO2: 0.1%–0.5%.

[0218] In one embodiment, the mass ratio of Al2O3 to Y2O3 can be 0.7-2. By controlling the ratio of Al2O3 to Y2O3, glass with stable properties can be prepared. If the ratio of Al2O3 to Y2O3 deviates too much, devitrification of the glass is likely to occur after melting, making it impossible to prepare transparent glass. In addition, controlling the ratio of Al2O3 to Y2O3 within the above range can also help control the size and amount of precipitated crystals, which is beneficial for subsequent ion exchange, so that the ion-exchanged glass-ceramic has a higher tensile stress linear density.

[0219] The molded glass sheet containing the above-mentioned components has a high elastic modulus, such as an elastic modulus greater than 90 GPa. Furthermore, the yttrium aluminum silicon glass of this application embodiment can undergo crystallization treatment and chemical strengthening treatment to further improve the mechanical properties of the yttrium aluminum silicon glass.

[0220] In one embodiment, the yttrium aluminum silicon glass of this application can be a microcrystalline glass. As a type of glass material, microcrystalline glass can achieve higher mechanical properties than amorphous glass through compositional design and controlled crystallization.

[0221] Existing yttrium aluminum silicon glass is typically amorphous. In the crystallization of microcrystalline glass using existing yttrium aluminum silicon glass formulations, the uncontrolled grain growth results in large and inconsistent grains, leading to low light transmittance and high haze, hindering their application in electronic devices. However, the yttrium aluminum silicon glass of this application, through a rational combination of components, allows for the production of microcrystalline glass with controllable grain size during the crystallization process.

[0222] In the yttrium aluminum silicon glass of this application embodiment, the crystalline phase is nanocrystalline, and the grain size of the crystalline phase is 10-200 nm. By controlling the grain size of the crystal to be at the nanoscale, the glass can maintain high mechanical properties and prevent the grain size from being too large, which would reduce the mechanical and optical properties of the glass. Exemplarily, the grain size of the crystalline phase can be any two values ​​between 10 nm, 30 nm, 50 nm, 70 nm, 100 nm, 120 nm, 150 nm, 170 nm, or 200 nm.

[0223] It is understood that the composition of glass-ceramics includes both amorphous and crystalline phases, with the amorphous phase filling the spaces between the crystalline phases and acting as a binder. In one embodiment of this application, the yttrium aluminum silicon glass contains a crystalline phase, which includes Zr. x Y y O 2x+1.5y , ZrO2, ZnAl2O4, MgAl2O4, Y2Si2O7, Y4Zr3O 12 Ba 0.808 Al 1.71 Si2.99 At least one of O8, spodumene, and quartz solid solution; the value of x ranges from 0.72 to 0.95, such as 0.72, 0.82, 0.85, 0.88, and 0.9; the value of y ranges from 0.06 to 0.28, such as 0.06, 0.08, 0.1, 0.12, 0.18, and 0.28. By generating the above-mentioned crystalline phase and controlling the grain size of the crystalline phase, the light transmittance of the microcrystalline glass can be effectively improved, and the haze of the microcrystalline glass can be reduced. The volume proportion of the crystalline phase in the yttrium aluminum silicon glass is 30% to 80%. By adjusting the volume proportion of the crystalline phase in the yttrium aluminum silicon glass, the light transmittance of the glass can be adjusted. When the volume proportion of the crystalline phase is low, the light transmittance of the glass can be relatively high, and it can be used in the display cover of terminal devices. When the volume proportion of the crystalline phase is high, the light transmittance of the glass is low, and it can be used in the back cover of terminal devices.

[0224] The yttrium aluminum silicon glass in this application embodiment can also be ion-exchanged to form chemically strengthened glass.

[0225] In one embodiment, chemically strengthened glass is obtained after ion exchange. During the ion exchange process, some Li and Na are replaced by K to form a stress layer. The chemically strengthened glass after ion exchange may include the following components in the following mass percentages:

[0226] In another embodiment, the yttrium aluminum silicon glass comprises the following components by weight percentage:

[0227] Y2O3: 30%–45%,

[0228] Al2O3: 15%–25%,

[0229] SiO2: 25%–40%,

[0230] ZrO2: 0.5%–8%,

[0231] P2O5: 0.1%–2%,

[0232] Li2O 0.5%–2%,

[0233] Na2O 0.1%~2%,

[0234] K2O 0.1%~2%,

[0235] The total content of Li₂O, Na₂O, and K₂O is 0.7–6 wt%.

[0236] MgO: 0.1%–6%,

[0237] ZnO: 0.5%–6%,

[0238] CaO: 0.1%–6%,

[0239] BaO: 0.1%–6%,

[0240] The total content of divalent metal oxides such as MgO, ZnO, CaO, and BaO is 0.%–20%.

[0241] TiO2: 0.05%–0.5%,

[0242] Sb₂O₃: 0.1%–0.5%,

[0243] CeO2: 0.1%–0.5%.

[0244] The chemically strengthened yttrium aluminum silicon glass of this application embodiment has a stress layer depth greater than or equal to 120 μm, thereby significantly improving the surface strength of the yttrium aluminum silicon glass. The tempered yttrium aluminum silicon glass of this application embodiment has an elastic modulus greater than or equal to 120 GPa, a compressive stress CS50 at 50 μm greater than 200 MPa, an average tensile stress CT.av in the tensile stress zone greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm, falling ball impact energy (also known as falling ball impact height) can be greater than 0.2J, transmittance is greater than 88%, and the drop failure height of 80-grit sandpaper is greater than 1.8m.

[0245] For the same technical purpose, this application also provides a method for preparing yttrium aluminum silicon glass, which includes the following steps:

[0246] A glass substrate is prepared, comprising the following components in the indicated mass percentages: Y₂O₃: 30%–45%, Al₂O₃: 15%–28%, SiO₂: 25%–45%, ZrO₂: 0.5%–8%, P₂O₅: 0.1%–2%, monovalent metal oxides: 0.5%–10 wt%, wherein the monovalent metal oxides include Li₂O, TiO₂: 0%–2%, Sb₂O₃: 0%–0.5%, CeO₂: 0%–0.5%, and divalent metal oxides: 0.1%–16%.

[0247] The glass substrate is subjected to a first heat treatment and a second heat treatment to obtain microcrystalline glass. The temperature of the first heat treatment is 600-800℃ and the heat treatment time is 0.5-60h. The temperature of the second heat treatment is 750-900℃ and the heat treatment time is 0.5-4h.

[0248] In one embodiment, the preparation method of this application further includes a chemical strengthening treatment step. The chemical strengthening treatment includes: the microcrystalline glass after a second heat treatment is then subjected to a first ion exchange treatment and a second ion exchange treatment sequentially.

[0249] The first ion exchange treatment includes: placing the microcrystalline glass in a first molten salt and exchanging it at 450-550°C for 1-20 hours; the first molten salt comprises the following components by weight percentage: 50-70 wt% sodium nitrate, 20-40 wt% potassium nitrate, 0-5 wt% lithium nitrate, 0.5-2 wt% alumina, 0.5-2 wt% diatomaceous earth, and 0.5-2 wt% antimony trioxide;

[0250] The second ion exchange treatment includes: placing the microcrystalline glass in a second molten salt and exchanging it at 480–600°C for 0.5–20 h; the second molten salt comprises the following components by weight percentage: 50–70 wt% potassium nitrate, 20–40 wt% sodium nitrate, 0–5 wt% cesium nitrate, 0.5–2 wt% alumina, 0.5–2 wt% diatomaceous earth, 0.5–2 wt% antimony trioxide, and 0.5–2 wt% potassium hydroxide.

[0251] For example, the method for preparing yttrium aluminum silicon glass according to embodiments of this application may include the following steps:

[0252] S1. Weigh the raw materials according to the required ratio, melt each raw material to obtain molten glass, and then process the molten glass to obtain glass sheets. In the melting stage, the glass raw materials are heated to 1500-1600℃ and held at that temperature for a certain time to melt. A suitable stirring process is adopted, and the cooling curve is designed and optimized to ensure that the glass forming can proceed smoothly and to eliminate micro-defects in the glass sheets.

[0253] The composition of the glass substrate is as follows: Y2O3: 30%–45%, Al2O3: 15%–28%, SiO2: 25%–45%, ZrO2: 0.5%–8%, P2O5: 0.1%–2%, monovalent metal oxides: 0.5%–10 wt%, wherein the monovalent metal oxides include Li2O, TiO2: 0%–2%, Sb2O3: 0%–0.5%, CeO2: 0%–0.5%, and divalent metal oxides: 0.1%–16%.

[0254] Yttrium aluminum silicon glass substrates with the above-mentioned ratios can have an elastic modulus of 90 GPa or even 100 GPa or higher, and have a suitable viscosity-temperature curve to ensure the smooth progress of melting and forming processes.

[0255] Among them, glass forming processes can include float glass forming, calendering, overflow forming, and drawing forming.

[0256] S2. Crystallization treatment: The glass substrate undergoes a first heat treatment and a second heat treatment to obtain microcrystalline glass. The temperature of the first heat treatment can be 600-800℃, or 600-720℃, or 600-750℃, and the heat treatment time can be 0.5-60h, for example, 10-60h, 20-60h, or 30-60h. The temperature of the second heat treatment is 750-900℃, or 780-900℃, or 800-900℃, and the heat treatment time is 0.5-4h, or 0.5-3h, or 0.5-2h.

[0257] The first heat treatment is a nucleation treatment, which allows the original glass sheet to fully nucleate, resulting in the precipitation of a large number of crystal nuclei. The second heat treatment is a crystallization treatment. Thanks to the thorough heat treatment in the nucleation stage, a large number of uniform crystal nuclei are precipitated in the glass, allowing a large number of uniformly distributed nanocrystals to precipitate in the crystallization stage. The volume ratio of crystals is kept in the range of 30-50%, thereby further improving the elastic modulus of the glass-ceramic, for example, the elastic modulus can exceed 120 GPa, or even 140 GPa or more.

[0258] S3. Strengthening treatment: The microcrystalline glass after the second heat treatment is then subjected to the first ion exchange treatment and the second ion exchange treatment in sequence.

[0259] The first ion exchange treatment includes: placing the microcrystalline glass in a first molten salt and exchanging it at 450-550°C for 1-20 hours; the first molten salt comprises the following components by weight percentage: 50-70 wt% sodium nitrate, 20-40 wt% potassium nitrate, 0-5 wt% lithium nitrate, 0.5-2 wt% alumina, 0.5-2 wt% diatomaceous earth, and 0.5-2 wt% antimony trioxide;

[0260] The second ion exchange treatment includes: placing the microcrystalline glass in a second molten salt and exchanging it at 480–600°C for 0.5–20 h; the second molten salt comprises the following components by weight percentage: 50–70 wt% potassium nitrate, 20–40 wt% sodium nitrate, 0–5 wt% cesium nitrate, 0.5–2 wt% alumina, 0.5–2 wt% diatomaceous earth, 0.5–2 wt% antimony trioxide, and 0.5–2 wt% potassium hydroxide.

[0261] The composition and preparation method of yttrium aluminum silicon glass have been explained above. The specific properties of the yttrium aluminum silicon glass of this application will be explained below with reference to specific embodiments.

[0262] The test methods used for each performance parameter in the following embodiments and comparative examples will be explained first.

[0263] Component determination: X-ray fluorescence spectroscopy combined with inductively coupled plasma emission spectroscopy was used to quantitatively analyze the chemical composition of the glass.

[0264] Crystal phase determination: X-ray diffraction combined with field emission scanning electron microscopy was used to analyze the type, size and distribution of glass crystal phases in order to confirm the microcrystalline glass phase and its distribution.

[0265] Elastic modulus: The elastic modulus was measured using an elastic modulus meter in accordance with GB / T 7962.6-2010.

[0266] Visible light transmittance: measured using a spectrophotometer in accordance with GB / T 2410-2008.

[0267] Mechanical property testing: The characteristic stress values ​​of chemically strengthened glass were tested using a diffuse light glass stress meter (e.g., SLP2000) and a surface stress meter (e.g., FSM6000). The FSM6000 was used to test the surface compressive stress CS, while the SLP2000 was used to test the compressive stress values ​​at different depths in the chemically strengthened glass, such as the compressive stress CS50 at 50 μm, the compressive stress layer thickness DOL, and the average tensile stress CT.av in the tensile stress zone.

[0268] Tensile stress density determination: The tensile stress density of the ion-exchanged glass-ceramic was measured using an electron probe combined with the FSM-6000le and SLP-2000.

[0269] Falling ball impact test: A steel ball with a diameter of φ20mm and a weight of 32.65g was used to impact the glass in free fall. The drop height h corresponding to glass breakage was recorded, and the impact energy was converted into the corresponding impact energy using the energy calculation formula: J = Mgh, where M is the mass of the steel ball, and g = 9.8m / s². 2 h is the glass failure height.

[0270] Drop Test: To test the drop resistance of the chemically strengthened glass from different embodiments and comparative examples on rough surfaces, the obtained chemically strengthened glass was assembled into a commercial mobile phone. The failure height was tested using a drop tester on controlled surfaces of 80-grit SiC sandpaper and 180-grit SiC sandpaper. The initial drop height was 0.6m, gradually increased to 2.5m in 0.1m increments. The failure height was defined as the height H at which the glass screen shattered. To obtain the average failure height of the cover glass from the embodiments and comparative examples, at least five cover glass pieces were selected for five-drop tests.

[0271] Examples 1-5

[0272] Examples 1-5 are yttrium aluminum silicon glasses, in which the mass percentage of Y₂O₃ is greater than or equal to 30%. The specific composition and preparation process parameters are listed in Table 1. Various properties of the yttrium aluminum silicon glasses in Examples 1-5 were tested, and the test results are listed in Table 1.

[0273] The method for preparing yttrium aluminum silicon glass according to embodiments of this application may include the following steps:

[0274] S1. Weigh the raw materials according to the required ratio, melt each raw material to obtain molten glass, and then process the molten glass to obtain glass sheets. In the melting stage, the glass raw materials are heated to 1500-1600℃ and held at that temperature for a certain time to melt. A suitable stirring process is adopted, and the cooling curve is designed and optimized to ensure that the glass forming can proceed smoothly and to eliminate micro-defects in the glass sheets.

[0275] S2. Crystallization treatment: The glass substrate is subjected to a first heat treatment and a second heat treatment to obtain microcrystalline glass. The temperature of the first heat treatment can be 600-800℃ and the heat treatment time can be 30-60h; the temperature of the second heat treatment is 750-900℃ and the heat treatment time is 0.5-2h.

[0276] S3. Strengthening treatment: The microcrystalline glass after the second heat treatment is then subjected to the first ion exchange treatment and the second ion exchange treatment in sequence.

[0277] The first ion exchange treatment includes: placing the microcrystalline glass in a first molten salt and exchanging it at 450-550°C for 1-20 hours; the first molten salt comprises the following components by weight percentage: 50-70 wt% sodium nitrate, 20-40 wt% potassium nitrate, 0-5 wt% lithium nitrate, 0.5-2 wt% alumina, 0.5-2 wt% diatomaceous earth, and 0.5-2 wt% antimony trioxide;

[0278] The second ion exchange treatment includes: placing the microcrystalline glass in a second molten salt and exchanging it at 480–600°C for 0.5–20 h; the second molten salt comprises the following components by weight percentage: 50–70 wt% potassium nitrate, 20–40 wt% sodium nitrate, 0–5 wt% cesium nitrate, 0.5–2 wt% alumina, 0.5–2 wt% diatomaceous earth, 0.5–2 wt% antimony trioxide, and 0.5–2 wt% potassium hydroxide.

[0279] Comparative Examples 1-5

[0280] Comparative Examples 1-5 are yttrium aluminum silicon glasses, in which the mass percentage of Y₂O₃ is less than 30%. Their specific composition and preparation process parameters are listed in Table 2. Various properties of the yttrium aluminum silicon glasses in Comparative Examples 1-5 were tested, and the test results are listed in Table 2.

[0281] Comparative Examples 6-7

[0282] Comparative Examples 6 and 7 are yttrium aluminum silicon glasses, in which the mass percentage of Y₂O₃ is less than 30%. Their specific composition and preparation process parameters are listed in Table 3. Various properties of the yttrium aluminum silicon glasses in Comparative Examples 6 and 7 were tested, and the test results are listed in Table 3.

[0283] The preparation methods for Comparative Examples 1-7 can refer to the preparation methods for Examples 1-5.

[0284] Table 1

[0285]

[0286]

[0287] In Table 1, the proportions of other elements after the exchange also changed slightly. They are not shown in the table, only the contents of Li, Na and K ions after the exchange are shown.

[0288] Table 2

[0289]

[0290]

[0291] In Table 2, the proportions of other elements after the exchange also changed slightly. They are not shown in the table; only the contents of Li, Na, and K ions after the exchange are shown.

[0292] Table 3

[0293]

[0294]

[0295] In Table 3, the proportions of other elements after the exchange also changed slightly. They are not shown in the table, only the contents of Li, Na and K ions after the exchange are shown.

[0296] As shown in Table 1, Examples 1-5 have an elastic modulus exceeding 140 GPa, a stress layer depth exceeding 140 μm, a Cs50 greater than 200 MPa, a CT.av greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4MPa / mm, drop ball impact height greater than 0.2J, transmittance exceeding 88%, and overall drop height exceeding 1.8m (180-grit sandpaper). Table 2 shows that the elastic modulus of the yttrium aluminum silicon glass in Comparative Examples 1-5 did not exceed 140 GPa, and the stress layer depth did not exceed 120 μm. Among them, compared to Comparative Examples 1-5, the yttrium aluminum silicon glass in Examples 1-5 had a yttrium oxide content of 30 wt% or higher, and incorporated divalent metal oxides such as ZnO, MgO, and BaO for co-doping, resulting in superior mechanical properties, an elastic modulus reaching 140 GPa, and an overall drop height below 1.8m (180-grit sandpaper).

[0297] Table 3 shows that when yttrium oxide contains aluminum within the range of this application, while alumina and silicon oxide are not within the range defined in this application, it will lead to difficulties in forming glass-ceramics, a decrease in transmittance, a smaller total amount of precipitated crystals, a lower crystal content, a worse ion exchange effect, a lower resistance to falling ball impact energy, and a lower drop height of only 1.1-1.6m.

[0298] The yttrium aluminum silicon glass of this application has a higher Y₂O₃ content, resulting in a denser glass structure. Furthermore, by introducing a suitable nucleating agent and designing a reasonable heat treatment process, uniformly distributed nanoscale crystals can be precipitated within the glass, forming a microcrystalline glass with multiple composite crystal phases, leading to higher mechanical properties after crystallization. In the preparation method of this application, a "long nucleation, short crystallization" heat treatment regime is used to precipitate uniformly distributed nanocrystalline crystals. In addition, through a reasonable molten salt ratio and ion exchange process, higher surface stress and deeper ion exchange can be obtained, enabling the glass's elastic modulus to exceed 140 GPa.

[0299] in, Figure 2 This is a differential scanning calorimeter (DSC) curve from Example 3. Figure 2 It can be seen that the temperature parameters such as melting point and phase transition temperature of the microcrystalline glass in the embodiments of this application are as follows. Figure 3 The images show the X-ray diffraction (XRD) patterns of the microcrystalline glass in Examples 2-5. Figure 4 The XRD patterns are for comparative examples 2-5. From... Figure 3 and Figure 4 As can be seen from the comparison, the crystal phase structure of the microcrystalline glass in the embodiments of this application is different from that of Comparative Examples 2-5. Figure 5 This is a SEM image of the microcrystalline glass of Example 5. From... Figure 5 As can be seen, the microcrystalline glass of this application embodiment can precipitate a crystalline phase with uniform grain size.

[0300] In summary, the yttrium aluminum silicon glass of this application has the following advantages:

[0301] The unique Y2O3-Al2O3-SiO2 (YAS) system glass composition makes its glass structure relatively dense, and the elastic modulus of the parent glass itself is greater than 90 GPa, which is greater than that of ordinary high-alumina glass and lithium aluminum silicon glass.

[0302] During the crystallization process, a heat treatment regime involving low-temperature, long-term phase separation and nucleation, followed by high-temperature, rapid crystallization, precipitates 30-80% by volume nanoscale crystals in the glass-ceramic, along with 20-70% by volume residual glass phase. This residual glass phase exhibits a high alumina content and low levels of alkali metal oxides and alkaline earth alkali metal oxides, resulting in a unique network structure that facilitates ion exchange. In contrast, existing yttrium aluminum silicon glass, due to its unique glass phase structure, cannot undergo ion exchange, thus preventing the production of reinforced glass with a high surface stress layer.

[0303] In this embodiment, addressing the issue of high temperatures during the ion exchange process of YAS microcrystalline glass, a molten salt ratio was designed. In addition to adding potassium hydroxide as an accelerator, antimony trioxide was added to adsorb oxygen generated from nitrate decomposition, preventing oxygen from adhering to the microcrystalline glass surface and promoting efficient ion exchange. Through a reasonable molten salt ratio and appropriate ion exchange temperature and time, the exchanged microcrystalline glass exhibits an ion exchange depth exceeding 120 μm, a Cs50 greater than 200 MPa, a CT.av greater than 100 MPa, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm. Furthermore, the final result can achieve a drop height of more than 0.2J for the microcrystalline glass ball, a transmittance of more than 88%, and a drop height of more than 1.8m (80-grit sandpaper).

[0304] The above are merely specific embodiments of this application, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

Claims

1. A yttrium aluminum silicon glass, characterized in that, The yttrium aluminum silicon glass comprises the following components by weight percentage: Y2O3: 30%–45%, Al2O3: 15%–28%, SiO2: 25%–45%, ZrO2: 0.5%–8%, P2O5: 0.1%–2%, Monovalent metal oxides: 0.5–10 wt%, including Li₂O. TiO2: 0%–2%, Sb₂O₃: 0%–0.5%, CeO2: 0%–0.5%, Divalent metal oxides: 0.1%–16%.

2. The yttrium aluminum silicon glass according to claim 1, characterized in that, In the yttrium aluminum silicon glass, the mass percentage of Y₂O₃ is 32% to 45%.

3. The yttrium aluminum silicon glass according to claim 1 or 2, characterized in that, In the yttrium aluminum silicon glass, the mass percentage of Al2O3 is 15% to 25%.

4. The yttrium aluminum silicon glass according to any one of claims 1-3, characterized in that, In the yttrium aluminum silicon glass, the mass percentage of SiO2 is 25% to 40%.

5. The yttrium aluminum silicon glass according to any one of claims 1-4, characterized in that, The divalent metal oxide includes at least one of MgO, CaO, ZnO, and BaO.

6. The yttrium aluminum silicon glass according to any one of claims 1-5, characterized in that, The yttrium aluminum silicon glass comprises the following components by weight percentage: Y2O3: 30%–45%, Al2O3: 15%–25%, SiO2: 25%–40%, ZrO2: 0.5%–8%, P2O5: 0.1%–2%, Monovalent metal oxides: 1.0–10%, wherein the monovalent metal oxides include Li₂O and Na₂O, wherein the mass percentage of Li₂O is 0.5–6%, and the mass percentage of Na₂O is 0.5–6%. TiO2: 0%–2%, Sb₂O₃: 0%–0.5%, CeO2: 0.1%–0.5%, Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

7. The yttrium aluminum silicon glass according to any one of claims 1-6, characterized in that, The elastic modulus of the yttrium aluminum silicon glass is greater than 90 GPa.

8. The yttrium aluminum silicon glass according to any one of claims 1-7, characterized in that, The yttrium aluminum silicon glass is a microcrystalline glass, and the yttrium aluminum silicon glass contains a crystalline phase, which includes Zr. x Y y O 2x+1.5y , ZrO2, ZnAl2O4, MgAl2O4, Y2Si2O7, Y4Zr3O 12 Ba 0.808 Al 1.71 Si 2.99 At least one of O8, spodumene, and quartz solid solution; the value of x ranges from 0.72 to 0.95, and the value of y ranges from 0.06 to 0.28; The crystalline phase accounts for 30-80% of the volume of the yttrium aluminum silicon glass.

9. The yttrium aluminum silicon glass according to claim 8, characterized in that, The crystalline phase is nanocrystalline, and the grain size of the crystalline phase is 10-200 nm.

10. The yttrium aluminum silicon glass according to any one of claims 1-9, characterized in that, The yttrium aluminum silicon glass is a chemically tempered glass, and the yttrium aluminum silicon glass comprises the following components by weight percentage: Y2O3: 30%–45%, Al2O3: 15%–28%, SiO2: 25%–45%, ZrO2: 0.5%–8%, P2O5: 0.1%–2%, Monovalent metal oxides: 1.5–10%, wherein the monovalent metal oxides include Li₂O, Na₂O, and K₂O, wherein the mass percentage of Li₂O is 0.5–6%, the mass percentage of Na₂O is 0.5–6%, and the mass percentage of K₂O is 0.5–6%. TiO2: 0%–2%, Sb₂O₃: 0%–0.5%, CeO2: 0.1%–0.5%, Divalent metal oxides: 0.5% to 16%, wherein the divalent metal oxides include ZnO, and the mass percentage of ZnO is 0.5% to 16%.

11. The yttrium aluminum silicon glass according to claim 10, characterized in that, The stress layer depth of the yttrium aluminum silicon glass is greater than or equal to 120 μm.

12. The yttrium aluminum silicon glass according to any one of claims 8-11, characterized in that, The yttrium aluminum silicon glass has an elastic modulus greater than or equal to 140 GPa, a compressive stress CS50 at 50 μm greater than 200 MPa, an average tensile stress CT.av greater than 100 MPa in the tensile stress zone, and a tensile stress linear density greater than 1.5 × 10⁻⁶. 4 MPa / mm, falling ball impact energy greater than 0.2J, transmittance greater than 88%, drop failure height of 80-grit sandpaper surface greater than 1.8m.

13. A method for preparing yttrium aluminum silicon glass, characterized in that, include: A glass substrate is prepared, comprising the following components in the indicated mass percentages: Y₂O₃: 30%–45%, Al₂O₃: 15%–28%, SiO₂: 25%–45%, ZrO₂: 0.5%–8%, P₂O₅: 0.1%–2%, monovalent metal oxides: 0.5%–10 wt%, wherein the monovalent metal oxides include Li₂O, TiO₂: 0%–2%, Sb₂O₃: 0%–0.5%, CeO₂: 0%–0.5%, and divalent metal oxides: 0.1%–16%. The glass substrate is subjected to a first heat treatment and a second heat treatment to obtain microcrystalline glass. The temperature of the first heat treatment is 600-800℃ and the heat treatment time is 0.5-60h. The temperature of the second heat treatment is 750-900℃ and the heat treatment time is 0.5-4h.

14. The preparation method according to claim 13, characterized in that, The preparation method further includes the step of subjecting the microcrystalline glass after the second heat treatment to a first ion exchange treatment and a second ion exchange treatment in sequence; The first ion exchange treatment includes: placing the microcrystalline glass in a first molten salt and exchanging it at 450-550°C for 1-20 hours; the first molten salt comprises the following components by weight percentage: 50-70 wt% sodium nitrate, 20-40 wt% potassium nitrate, 0-5 wt% lithium nitrate, 0.5-2 wt% alumina, 0.5-2 wt% diatomaceous earth, and 0.5-2 wt% antimony trioxide; The second ion exchange treatment includes: placing the microcrystalline glass in a second molten salt and exchanging it at 480–600°C for 0.5–20 h; the second molten salt comprises the following components by weight percentage: 50–70 wt% potassium nitrate, 20–40 wt% sodium nitrate, 0–5 wt% cesium nitrate, 0.5–2 wt% alumina, 0.5–2 wt% diatomaceous earth, 0.5–2 wt% antimony trioxide, and 0.5–2 wt% potassium hydroxide.

15. A display screen, characterized in that, Includes yttrium aluminum silicon glass as described in any one of claims 1-12, or yttrium aluminum silicon glass obtained by the preparation method as described in claim 13 or 14.

16. A structural component, characterized in that, Includes yttrium aluminum silicon glass as described in any one of claims 1-12, or yttrium aluminum silicon glass obtained by the preparation method as described in claim 13 or 14.

17. An electronic device, characterized in that, Includes the display screen as described in claim 15 or the structural component as described in claim 16.